Higher initial levothyroxine doses and very early treatment start may lead to better cognitive outcomes in children with congenital hypothyroidism - Danner, Emmi; Niuro, Laura; Lapinoja, Sonja; Huopio, Hanna; Viikari, Liisa A.; Kero, Jukka; Jääskeläinen, Jarmo; Niinikoski, Harri (Wiley, 2026)
Aim
This study aimed to assess the cognitive development of individuals with congenital hypothyroidism.
Methods
Using hospital records, we identified 180 patients with congenital hypothyroidism born between 1980 and 2018 in Turku and Kuopio University Hospital catchment areas. Cognitive development was evaluated in 22 adults (7 males and 15 females) and 20 children (8 males and 12 females) using age-specific Wechsler Intelligence Scales. Full-scale IQ (FSIQ) and the four indices were compared to standardisation samples. Simple linear regression was used to test whether treatment-related variables predicted FSIQ.
Results
FSIQ and its four indices differed significantly from the standardisation sample in adults with congenital hypothyroidism (FSIQ 87.64, SD 13.70, p < 0.001) but not in children (FSIQ 97.90, SD 15.12). Adults had received a lower initial levothyroxine dose than children (8.1 mg/kg, 95% CI 7.2–9.0 vs. 10.2 mg/kg 9.7–10.7, p < 0.001), and their treatment was initiated later (4.8 days, 95% CI 4.0–5.6 vs. 3.6 days, 2.9–4.2, p = 0.018).
Conclusion
Adults with congenital hypothyroidism had a significantly lower FSIQ compared to the population standard, while children's FSIQ did not differ. Our findings suggest that a higher initial levothyroxine dose together with very early treatment start may lead to better cognitive outcomes.